Pelatihan Kemampuan Literasi Bahasa dan Sastra Berbasis karakter di PKBM At-taubah lapas II B Cianjur - Adawiyah, Aprilla; Maryam, Siti; Diningsih, Cinde Adia; Hasanah, Aan; Supriatna, Agus; Putra, Mochamad Aditya Dwi (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
This paper delves into the outcomes of a training program aimed at enhancing language and literary literacy skills among inmates at PKBM At-Taubah Lapas II B Cianjur. These literacy skills are crucial for inmates' success in both the workplace and within their communities. The training program was structured into three distinct classes: language, character development, and literary development (poetry musicalization). The target participants were 25 inmates. Throughout the training, the inmates actively engaged in the learning activities. In the language class, while their speaking abilities were generally satisfactory, not all inmates were comfortable presenting in front of the class. Only three inmates volunteered to present when asked. In the character development and poetry musicalization classes, inmates were divided into groups and tasked with creating a musicalized poem. While their public speaking skills in the context of language literacy still require improvement due to confidence issues, the inmates successfully produced a group performance of their musicalized poetry creations.